Establishment of flood damage function model for urban area in Kuantan: A preliminary study - N. S., Romali; Z., Yusop (IOP Publishing, 2021)
Previous studies on flood damage assessment mostly discussed the relationship between flood damages and hydrological impacts parameters such as flood depth and flood duration. The influence of resistance parameters on flood damages is rarely investigated. Hence, an attempt has been made to establish a flood damage function model based on the relationships between flood damages and the variables of socio-economic and property characteristics for an urban area in Kuantan. Using a face to face interview technique, a field survey was conducted to gather damage data and related information from the 2013 Kuantan flood. Damages to residential structures were found to be influenced by household income, type of construction materials, and house level. On the other hand, household income, house type, and occupation were identified as the most significant variables that influenced the damages of residential content. For the commercial category, only the areas of the premises were significantly affected by the various structural damages, whereas the content damages depended mostly on the type of business, the surrounding areas, and the premises' number of floors. The relationship between flood damages and their influencing factors is important and should be further tested before proceeding with any application on a wider scale.